A simple model for transit dosimetry based on a water equivalent EPID. Issue 3 (24th January 2018) - Deshpande, S.; Blake, S. J.; Xing, A.; Metcalfe, P. E.; Holloway, L. C.; Vial, P.
Abstract : Purpose: The aim of this study was to demonstrate a new model for implementing a transit dosimetry system as a means of in vivo dose verification with a water equivalent electronic portal imaging device (WE‐EPID) and a conventional treatment planning system (TPS). Method and materials: A standard amorphous silicon (a‐Si) EPID was modified to a WE‐EPID configuration by replacing the metal‐plate/phosphor screen situated above the photodiode detector with a 3 cm thick water equivalent plastic x ray converter material. A clinical TPS was used to calculate dose to the WE‐EPID in its conventional EPID position behind the phantom/patient. The "extended phantom" concept was used to facilitate dose calculation at the EPID position, which is outside the CT field of view (FOV). The CT images were manipulated from 512 × 512 into 1024 × 1024 and padded pixels were assigned the density of air before importing to the TPS. The virtual WE‐EPID was added as an RT structure of water density at the EPID plane. The accuracy of TPS dose calculations at the EPID plane in transit geometry was first evaluated for different field sizes and thickness of object in the beam by comparison with the dose measured using a 2D ion chamber array (ICA) and the WE‐EPID. Following basic dose response tests, clinical fields including direct single fields (open and wedged) and modulated fields (integrated or control point by control point doses for VMAT) were measured for 6 MV photons with varying of solid water thickness or an anthropomorphic phantom present in beam. The EPID images were corrected for dark signal and pixel sensitivity and converted to dose using a single dose calibration factor. The 2D dose evaluation was conducted using 3%/3 and 2%/2 mm gamma‐index criteria. Results: The measured dose–response with the ICA and WE‐EPID for all basic dose–response tests agreed with TPS dose calculations to within 1.5%. The maximum difference in dose profiles for the largest measured field size of 25 × 25 cm 2 was 2.5%. Gamma evaluation showed at least 94% (3%/3 mm criteria) and 90% (2%/2 mm) agreement in both integrated and control‐point doses for all clinical fields acquired by the WE‐EPID and ICA when compared with TPS‐calculated portal dose images. Conclusion: A new approach to transit dose verification has been demonstrated utilizing a water equivalent EPID and a commercial TPS. The accuracy of dose calculations at the EPID plane using a commercial TPS beam model was experimentally confirmed. The model proposed in this study provides an accurate method to directly verify doses delivered during treatment without the additional uncertainties inherent in modelling the complex dose–response of standard EPIDs.